Defining mesenchymal stromal cell (MSC)-derived small extracellular vesicles for therapeutic applications. Issue 1 (1st January 2019) - Witwer, Kenneth W.; Van Balkom, Bas W.M.; Bruno, Stefania; Choo, Andre; Dominici, Massimo; Gimona, Mario; Hill, Andrew F.; De Kleijn, Dominique; Koh, Mickey; Lai, Ruenn Chai; Mitsialis, S. Alex; Ortiz, Luis A.; et al.
ABSTRACT: Small extracellular vesicles (sEVs) from mesenchymal stromal/stem cells (MSCs) are transiting rapidly towards clinical applications. However, discrepancies and controversies about the biology, functions, and potency of MSC-sEVs have arisen due to several factors: the diversity of MSCs and their preparation; various methods of sEV production and separation; a lack of standardized quality assurance assays; and limited reproducibility of in vitro and in vivo functional assays. To address these issues, members of four societies (SOCRATES, ISEV, ISCT and ISBT) propose specific harmonization criteria for MSC-sEVs to facilitate data sharing and comparison, which should help to advance the field towards clinical applications. Specifically, MSC-sEVs should be defined by quantifiable metrics to identify the cellular origin of the sEVs in a preparation, presence of lipid-membrane vesicles, and the degree of physical and biochemical integrity of the vesicles. For practical purposes, new MSC-sEV preparations might also be measured against a well-characterized MSC-sEV biological reference. The ultimate goal of developing these metrics is to map aspects of MSC-sEV biology and therapeutic potency onto quantifiable features of each preparation.